Current situation and future development of the biopharmaceutical industry in China: A mixed-method study - Yang, Ruomeng; Kabba, John Alimamy; Yao, Xuelin; Yang, Caijun; Chang, Jie; Ji, Wenjing; Jiang, Minghuan; Zhao, Mingyue; Wen, Jun; Fang, Yu (Frontiers in Pharmacology, 2022)
Introduction The biomedical industry has grown significantly both globally and in China. However, there are still challenges. This study evaluates China's biopharmaceutical industries' ability to innovate, sales volume, investment, and R&D expenditure, as well as a case study of Shaanxi province. Method A cross-sectional study design was used to generate a comprehensive profile of the nature of biopharmaceutical innovation capacity and development by triangulating qualitative and quantitative data. Only biopharmaceutical companies that are currently marketing or conducting research and development were eligible for inclusion. Categorical and continuous variables were analyzed descriptively. Interviews were thematically analyzed using NVivo version 12. Results The analysis includes a response from 77 biopharmaceutical enterprises. The majority are from Eastern China, 36 (46.8%), followed by Central 26 (33.8%). In 2018, total sales amounted to 26.28 billion yuan, and in 2019, a slight increase was observed (30.34 billion), which doubled in 2020 to about 67.91 billion yuan. The top three biopharmaceutical products on sale in 2020 were Camrelizumab (5.14 billion yuan), human albumin (4.56 billion yuan), and Human immunoglobulin for injection (3.78 billion yuan). Expenditure on R & D is also increasing, amounting to 1657.7 million yuan in 2018, and more than doubled in 2019, at 3572.1 million yuan, and further increased to 5857.7 million yuan in 2020. Nonetheless, the progress is not uniform across all provinces because of the lack of local government policies that will impact on funding, incentives, and market share that motivate the producers. Conclusions China's biopharmaceutical industry has expanded significantly. The increase in sales indicates that there is an increase in demand for biologicals, moreover, R&D funding is increasing, all of which are key indicators that influence innovation and development. However, the sector's capacity for innovation and development needs to be strengthened further, particularly in the western region, where research and production are relatively weak.